(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This study examines the effect of pre-heat treatment on laser engraving of aspen thermowood. We used an infrared CO2 laser with a wavelength of 10640 nm to engrave aspen thermowood samples with different pre-treatment temperatures, including one non-treated sample (base). The samples had a similar moisture content of about 6 - 8%, but exhibited different shades of brown depending on the pre-treatment temperature. The engraving depth and width were measured for each sample, and 8 graphs were constructed to analyze the results. Our findings show that pre-treatment temperature has a significant effect on the efficiency of laser engraving, with higher pre-treatment temperatures resulting in deeper engraving lines. The study provides valuable insights into the optimization of laser engraving parameters for aspen thermowood, and demonstrates the potential of pre-heat treatment to improve the quality of laser-engraved wooden products.